Pengembangan Media Audiovisual Berbasis Kearifan Lokal pada Siswa Sekolah Dasar - Zainab, Zainab; Pirol, Abdul; Suryani, Lilis (South Sulawesi Education Development, 2024)
This research explores the needs analysis, design, validity, and practicality of audiovisual media focused on the theme